Development and evaluation of PCR assay for detection of low levels of Cowdria ruminantium infection in Amblyomma ticks not detected by DNA probe. - Peter, T F (1995)
The sensitivities of a PCR assay and a DNA probe assay were compared for the detection of Cowdria ruminantium in Amblyomma ticks that were fed on C. ruminantium-infected, clinically reacting, and recovered carrier animals. The PCR assay and DNA probe detected infection in 86.0 and 37.0%, respectively, of 100 ticks fed on a febrile animal. In 75 ticks fed on carrier animals, PCR and the DNA probe detected infection in 28.0 and 1.33% of ticks, respectively. This demonstrates that the DNA probe has poor sensitivity for the detection of low levels of infection in ticks and that PCR is necessary for this purpose. The PCR assay had a detection limit of between 1 and 10 C. ruminantium organisms and did not amplify DNA from Ehrlichia canis, which is phylogenetically closely related to C. ruminantium, Theileria parva, or uninfected Amblyomma hebraeum or A. variegatum. PCR detected infection in A. hebraeum and A. variegatum adult ticks infected with one of six geographically different C. ruminantium strains. Amplification was also possible from desiccated ticks and ticks fixed in 70% ethanol, 10% buffered formalin, or 2% glutaraldehyde. The PCR assay supersedes the DNA probe and older detection methods for the detection of C. ruminantium in ticks, particularly those fed on carrier animals, and is suitable for both prospective and retrospective studies which require accurate detection of C. ruminantium in individual ticks. Application of the PCR assay should significantly improve the understanding of heartwater epidemiology, particularly through the determination of field tick infection rates.